Development of Ethnoscience Picture Storybooks as Learning Media in Understanding Science Concepts in Elementary Schools - Viola Emylia; Arinta Rezty Wijayaningputri (Postgraduate, University of Mataram, 2025)
This study aims to develop and test the effectiveness of an ethnoscience-based picture storybook to improve the understanding of science concepts in third-grade students of SDN 2 Landungsari, where learning has been limited to textbooks and minimal digital media. The book, entitled “Learning Science and Indonesian Culture with Lintang,” was developed by combining daily stories of the character Lintang, science concepts, and local culture, supported by engaging illustrations. Validation by media and material experts showed average scores of 90.63% and 82.64%, respectively, confirming that the book is suitable for use. The trial showed very positive student and teacher responses (98% and 100%). Students stated that the engaging story and illustrations helped them understand the material, while teachers considered the book effective in supporting learning. Statistical analysis showed a significant increase between the pre-test (mean = 43.64) and post-test (mean = 82.73; t = 4.08; p < 0.05), with an average N-gain of 0.63, which is included in the medium-high category. These results indicate that ethnoscience-based picture storybooks are effective in improving scientific understanding, offering concrete learning media for schools that lack facilities, and utilizing the potential of Nusantara culture as an engaging and meaningful learning resource.